Facial volumization an anatomic approach - Lamb, Jerome Paul; Surek, Christopher Chase (Thieme, 2018)
The gliding nature and dynamic planes of the face present one of the great challenges in aesthetic surgery and volume replenishment is a key component of the treatment algorithm. Facial Volumization: An Anatomic Approach by Jerome Lamb and Christopher Surek masterfully bridges the gap between the anatomy lab and injection clinic. It synthesizes a large body of facial anatomy publications into a ""one-stop shop"" covering a wide array of facial procedures - from the chin and perioral - to the midface and temple. In addition to vascular injury, lymphatic disruption can play a critical role in su